I would like to rearrange the equation:
X = (Y-A)/(Y-B) to look like this
B-A = ((X-1)*(Y-A))/X
I'm able to isolate B-A on the left hand side of the equation, but I
can't seem to get the right hand side to the form above.
I've tried the following steps:
1. XY-XB = Y-A
2. XY-XB-Y = -A
3. XY-Y = XB-A
4. XY-Y = X(B-(A/X))
5. (XY-Y)/X = B-(A/X)
6. B = (XY-Y)/X + (A/X) = (XY-Y+A)/X
7. B-A = ((XY-Y+A)/X)-A
and this is where I get stuck. I feel like I'm close but I can't
quite get it in the form shown above. What am I missing?